Persepsi Teknologi Informasi, Persepsi Kemudahan, Persepsi Kegunaan Terhadap Kepuasan Penggunaan E-wallet ShopeePay - Andi Aulia; Tuti Wediawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research aims to determine the influence of perceptions of information technology, perceptions of convenience, perceptions of usefulness on satisfaction with using the ShopeePay e-wallet, both simultaneously and partially. The sample in this study was 100 respondents and the data collection technique used a survey technique using a questionnaire. Sampling was carried out using a non-probability sampling technique which was used with purposive sampling. The research results show that simultaneously the variables perception of information technology, perception of convenience, perception of usefulness have a significant influence on satisfaction with using the ShopeePay e-wallet. Then, partially, the variable perception of information technology has a significant effect on satisfaction with using the ShopeePay e-wallet with a significance level of <0.001, the variable perception of convenience partially shows a significant effect on satisfaction with using the ShopeePay e-wallet with a significant level of 0.002, and the variable perception of usefulness partially shows that it has no significant effect on satisfaction with using the ShopeePay e-wallet with a significance level of 0.101. The large influence of perception of information technology, perception of convenience, perception of usefulness on ShopeePay e-wallet satisfaction is shown by the coefficient of determination of 0.615 or 61.5% where the ability of the independent variables in this research is perception of information technology, perception of convenience, perception of usefulness together. The same thing in explaining satisfaction with using the ShopeePay e-wallet as the dependent variable is 0.615 or 61.5%, while the remaining 38.5% is influenced by other variables outside the regression model of this research